Il paese mancato di Piero Gobetti. Il problema italiano - Perazzoli, Giovanni (Incontri. Rivista europea di studi italiani, 2011)
Piero Gobetti’s ‘failed nation’ The article aims to expounds the essence of Piero Gobetti’s analysis of Italian politics between the Risorgimento and Fascism. According to Gobetti, Italy never had a ‘liberal revolution’, which is why liberalism reappears in Italy in its original form, i.e. as a revolutionary doctrine. The weakness of this liberalism is reflected in moral and political weakness. The article seeks to demonstrate how, for Gobetti, Italian politics keep returning to the same themes, as it has traditionally been perceived in Italian political literature from Machiavelli to Benedetto Croce. Gobetti is, in this sense, both classical and modern. The combination of liberalism and republicanism is a characteristic of his analysis that helps one understand the prominence of political and civil discourse in Italy, a country that has had no religious reform, but at the same time had a secular political theory. Nevertheless, this combination, which remains elitist, is powerless to effect change, alien as it is to the rest of the political corpus. Gobetti’s œuvre typifies the idea of Italian political and moral history that divides Italy into two opposing parts. Fascism frequently represents one of the two poles.